Scouting for Citrus Greening - Jamie D. Yates; Stephen H. Futch; Timothy M. Spann (EDIS)
HS-1147, a 6-page illustrated fact sheet by Jamie D. Yates, Stephen H. Futch, and Timothy M. Spann, describes when to scout; different methods of scouting and their applications; symptoms of greening and how to distinguish these symptoms from those of other diseases/disorders; and what to do when a greening-infected tree is identified. Includes additional information. Published by the UF Department of Horticultural Sciences, August 2008.